Prevalence of total coliforms and Staphylococcus aureus in handlers of artisanal ice creams in Ancash, Peru - Alba L., Jeanne R. (2021)
Each department of Peru is characterized by offering a variety of regional dishes, desserts and drinks. Among these products are artisan ice creams based on milk cream and water, which must maintain a sanitary quality to prevent any foodborne disease, being prepared under good manufacturing practices and marketed according to general principles of hygiene. The objective of this study was to assess the effectiveness of hygiene practices through the quantification of total coliforms (TC) and Staphylococcus aureus (Sa) in the hands of artisan ice cream vendors in Caraz (n=22), Carhuaz (n=20) and Yungay (n=15), main cities of Callejón de Huaylas (Ancash) and compare them with the local legislation. The sampling method and microbiological analysis were carried out in accordance with Ministerial Resolution N° 461-2007/MINSA, where the maximum permissible limits for TC and Sa in handlers are indicated (<100 CFU/hands). The presence of TC and Sa was evidenced in the 40,4% (23/57) and 29,8% (17/57) of the evaluated samples, respectively, being out of regulation. Of the cities evaluated, Yungay was the one with the highest prevalence for both groups of indicator microorganisms (TC=80% and Sa=40%). The results obtained, show the need to work on an awareness and training program for ice cream vendors in those cities, focusing on creating a food safety culture based on the best handling practices.